Geohazard in Rocky Coastal Areas Special Publication: No.322 - Violante, C. (Geological Society Of London, 2012)
The reported case studies in the volume deal with land-born geological processes that deliver sediment to the coast and open sea at intermittent time intervals, often with catastrophic implications. They include large slope failures on both volcanic and non-volcanic coastal areas, cliff recession and floods of coastal streams from key areas of the Italian peninsula. All these studies seek to establish sea-land correlations based on marine geophysical investigations and field analyses, and to highlight the role of documentary sources in order to recognize geological constraints for hazard assessment in rocky coastal areas.